Mapping public policy options responding to obesity: The case of Morocco - Yahyane, Abdelhakim; Francis, Delpeuch; Ibrahmi, Btihaj Al; housni, Oumaima EL; Bour, Abdellatif (Edelweiss Applied Science and Technology, 2025)
Obesity is considered a chronic, progressive disease whose various factors can have serious consequences for metabolic and psychosocial health. The aim of this study was to map the viewpoints of stakeholders representing different sectors of activity on options for action by exploring concordances and divergences. We used multi-criteria mapping methodology during a structured interview with 33 stakeholders and defined five groups of options to address the problem of obesity. Four options stood out from all the others: the three options in the group of measures relating to education and training (in particular, reinforcing nutrition in the school curriculum and educating the public about health) and reinforcing physical activity in schools. With the exception of the agri-food sector for the training of health professionals and for physical activity in schools, all categories of stakeholders placed them at the top of their list of preferred measures in both optimistic and pessimistic scenarios. The study shows that there is broad agreement that only the implementation of a wide range of measures will be able to reverse the general trend towards rising obesity, even though measures aimed at changing behavior through education were ranked higher than those aimed at changing people’s environment.